Data from: Migratory culture, population structure and stock identity in North Pacific beluga whales (Delphinapterus leucas) ... - O'Corry-Crowe, Greg; Suydam, Robert; Quakenbush, Lori; Potgieter, Brooke; Harwood, Lois; Litovka, Dennis; Ferrer, Tatiana; Citta, John; Burkanov, Vladimir; Frost, Kathy; Mahoney, Barbara; O’Corry-Crowe, Greg (Dryad, 2019)
The annual return of beluga whales, Delphinapterus leucas, to traditional seasonal locations across the Arctic may involve migratory culture, while the convergence of discrete summering aggregations on common wintering grounds may facilitate outbreeding. Natal philopatry and cultural inheritance, however, has been difficult to assess as earlier studies were of too short a duration, while genetic analyses of breeding patterns, especially across the beluga's Pacific range, have been hampered by inadequate sampling and sparse information on wintering areas. Using a much expanded sample and genetic marker set comprising 1,647 whales, spanning more than two decades and encompassing all major coastal summering aggregations in the Pacific Ocean, we found evolutionary-level divergence among three geographic regions: the Gulf of Alaska, the Bering-Chukchi-Beaufort Seas, and the Sea of Okhotsk (Φst=0.11-0.32, Rst=0.09-0.13), and likely demographic independence of (Fst-mtDNA=0.02-0.66), and in many cases limited gene ... : GOCC-beluga whale genetic datacontains detailed genetic data on beluga whales, including GenBank accession numbers, mtDNA haplotype frequencies and microsatellite locus allele frequencies ...